Activities of C4 photosynthetic pathway enzymes in different bread wheat genotypes under field conditions - Daoura, Bachir Goudia; Saeed, Iqbal; Song, Quanhao; Yang, Yang; Chen, Liang; Hu, Yin-Gang (Penerbit Universiti Kebangsaan Malaysia, 2018)
The activities of key C4 photosynthetic enzymes including phosphoenolpyruvate carboxylase (PEPcase), NADP-malic enzyme (NADP-ME), malate dehydrogenase (MDH) and pyruvate phosphate dikinase (PPDK) were assayed in flag leaves at three major growth stages (heading, anthesis and grain filling) among 59 winter wheat genotypes grown in field conditions. All C4 enzymes expressed in the flag leaves and their activation showed a wide range of variation in relation to different growth stages in all the genotypes. PEPcase, NADP-ME and MDH displayed the highest mean activities of 1.018, 0.758 and 0.731 μmol. min–1.mg–1 protein at heading stage, respectively; while PPDK showed the highest mean activity (0.888 μmol. min–1.mg–1 protein) at grain filling stage. The activities of PEPcase and PPDK were higher at heading stage, decreased at anthesis and again increased at grain filling stage, while NADP-ME and MDH exhibited a decreasing trend at the three stages. The results of the current study could be valuable and useful for wheat researchers in improving photosynthetic capacity of wheat.